“So much worse for the facts(?)” – Fourteenth-Century Natural Philosophers and the Common Experience of Reaction - Podkoński, Robert (Roczniki Filozoficzne, 2025)
The article presents a selection of considerations by fourteenth-century Oxford and Paris scholars on the phenomena of common experience that seemingly confirm the occurrence of processes of reaction in rerum natura. All of the philosophers involved, however, attempted to explain these phenomena in such a way that allowed them to defend the statement of Aristotle that it is impossible that there be any such reaction, between either elementary or mixed bodies (mixta). On the basis of the explanations provided by these thinkers,one can arrive at the conclusion that they were simply unable to leave the boundaries of the Aristotelian worldview, at least with respect to the issue of mutual action of elementary bodies. In the final section of the article the plausible reasons for their attitude towards these phenomena of common experience are provided.